Price Discount: Pengaruhnya terhadap Online Customer Review dan Purchase Intention pada Konsumen Online Marketplace Platform pada Masa Pandemi Covid-19 - Subagio, Dyajeng Puteri Woro; Hastari, Sri (Jurnal Manajemen dan Kewirausahaan, 2021)
The COVID-19 pandemic significant impact on decreasing income and community activities, including shopping behavior. Many people have decided to use the online marketplace platform to shop for various needs. This study aims to investigate the direct and indirect relationships among variable price discounts, Online Customer Reviews (OCR), and purchase intentions for consumers of the 5 most popular online marketplace platforms in Indonesia during the COVID-19 pandemic. Collecting data in this study using an online questionnaire to 120 respondents as a sample who have met the purposive sampling criteria. This study uses Partial Least Square (PLS) to analyze the data. There is a uniqueness in this study where the price discount strategy is not able to directly influence consumer purchase intention even though the economic condition has decreased due to the pandemic. This strategy encourages consumers to seek information through online customer reviews. Information on OCR affects consumer purchase intention in a product. This makes OCR able to fully mediate the relationship between the price discount strategy and purchase intention.